2017
DOI: 10.3201/eid2304.161245
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium malariaePrevalence andcspGene Diversity, Kenya, 2014 and 2015

Abstract: In Africa, control programs that target primarily Plasmodium falciparum are inadequate for eliminating malaria. To learn more about prevalence and genetic variability of P. malariae in Africa, we examined blood samples from 663 asymptomatic and 245 symptomatic persons from western Kenya during June–August of 2014 and 2015. P. malariae accounted for 5.3% (35/663) of asymptomatic infections and 3.3% (8/245) of clinical cases. Among asymptomatic persons, 71% (32/45) of P. malariae infections detected by PCR were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
40
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 43 publications
8
40
0
1
Order By: Relevance
“…14 In Kenya, P. malariae was identified by molecular analysis in 5% of asymptomatic and 3% of symptomatic malaria infections. 15 In Uganda, molecular analysis of samples from a Kampala cohort for which genotyping did not identify P. falciparum suggested that 4.6% of plasmodial infections were due to P. malariae, 0.9% to P. ovale, and 0.5% to P. vivax. 16 A study of children from eastern Uganda noted frequent mixed infections when malaria was diagnosed by molecular methods, with 41% of infections P. falciparum and P. malariae, 9% P. falciparum and P. ovale, and 8% all three of these species.…”
Section: Introductionmentioning
confidence: 99%
“…14 In Kenya, P. malariae was identified by molecular analysis in 5% of asymptomatic and 3% of symptomatic malaria infections. 15 In Uganda, molecular analysis of samples from a Kampala cohort for which genotyping did not identify P. falciparum suggested that 4.6% of plasmodial infections were due to P. malariae, 0.9% to P. ovale, and 0.5% to P. vivax. 16 A study of children from eastern Uganda noted frequent mixed infections when malaria was diagnosed by molecular methods, with 41% of infections P. falciparum and P. malariae, 9% P. falciparum and P. ovale, and 8% all three of these species.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, using a panel of a few microsatellites, or sequencing a parasite antigen such as AMA-1 [22, 23], in most populations nearly every parasite sampled was different. While fewer studies were done on the population genetic composition of the other malaria parasite species infecting humans – Plasmodium ovale [24], Plasmodium malariae [25], and Plasmodium knowlesi [26] – they revealed important aspects about their biology. This included the finding that P. ovale is in fact two distinct parasite species – P. ovale curtisi and P. ovale wallikeri – which co-occur in many countries [24].…”
Section: Genotyping Malaria Parasites: Lessons Learned and The Way Fomentioning
confidence: 99%
“…Over the past decade, the world has experienced significant reduction in global falciparum malaria burden, but this decline was less prominent for the other human Plasmodium species [1]. Plasmodium malariae is endemic throughout parts of South America, Africa, Asia, and the Western Pacific [2,3,4].…”
Section: Introductionmentioning
confidence: 99%